Interferon-alpha subtype 11 activates NK cells and enables control of retroviral infection. - Kathrin Gibbert (Public Library of Science (PLoS), 2012)
The innate immune response mediated by cells such as natural killer (NK) cells is critical for the rapid containment of virus replication and spread during acute infection. Here, we show that subtype 11 of the type I interferon (IFN) family greatly potentiates the antiviral activity of NK cells during retroviral infection. Treatment of mice with IFN-α11 during Friend retrovirus infection (FV) significantly reduced viral loads and resulted in long-term protection from virus-induced leukemia. The effect of IFN-α11 on NK cells was direct and signaled through the type I IFN receptor. Furthermore, IFN-α11-mediated activation of NK cells enabled cytolytic killing of FV-infected target cells via the exocytosis pathway. Depletion and adoptive transfer experiments illustrated that NK cells played a major role in successful IFN-α11 therapy. Additional experiments with Mouse Cytomegalovirus infections demonstrated that the therapeutic effect of IFN-α11 is not restricted to retroviruses. The type I IFN subtypes 2 and 5, which bind the same receptor as IFN-α11, did not elicit similar antiviral effects. These results demonstrate a unique and subtype-specific activation of NK cells by IFN-α11.